Perdagangan Barang Startegis Di Era Digitalisasi: Telaah Regulasi, Dampak, dan Penegakan Hukumnya - Sabrinawati Saleh; Supriyadi A Arief (TERAJU: Jurnal Syariah dan Hukum, 2026)
The practice of trading strategic goods in the current digital era is crucial to examine in relation to government policies, particularly following the reciprocal agreement between the United States and Indonesia on import tariffs, which in practice was overturned by the United States Supreme Court. Therefore, a review will be conducted of the regulations, implications, and enforcement of existing laws in Indonesia. This issue will be examined using a qualitative, normative approach to analyse the legal issues governing the export and import of strategic goods in the digital era. The results of this study indicate that the regulation of strategic goods export and import activities in the digital era, as governed by the Trade Law, Customs Law, Electronic Information and Transactions Law, and technical implementing regulations, is crucial for maintaining business compliance, effective supervision, and protecting national interests. These regulations also enable the government to conduct more efficient supervision through digital systems, provide legal certainty, and prevent illegal trade practices. Consequently, law enforcement will encompass criminal sanctions, administrative sanctions, additional sanctions, and digital sanctions.